In their own voices: a study of former African American male athletes’ perceptions of their academic experiences at Michigan community colleges - Sabree, Yusuf (Kansas State University, 2022)
The purpose of this qualitative study was to explore the experiences of African American male former community college student-athletes who succeeded on their educational pathway. The study also sought to identify the supportive services African American male former student-athletes reported as contributing to their academic success. For the purpose of this study, educational pathway success meant the student earned either a certificate, an associate degree, or transferred to a four-year educational institution. Tinto’s theory of retention served as the study’s theoretical framework. A qualitative methodological approach was used involving a set of 11 interview questions with 16 African American male student-athletes, all of whom graduated from Michigan community colleges. Community colleges were chosen because the literature review showed high percentages of African American male student-athletes enrolled in community colleges are a vastly understudied population. Nine themes emerged from the analysis of the data. The data revealed the academic barriers participants endured while enrolled in community college, and the influence of family, teammates, coaches, faculty, and staff on their academic success. It is believed that, by understanding those factors that most influence an African American male student-athletes success in community college, both administrators and others who have a stake in this population’s understand the persistence that leads to the participants’ completion. Future research might include interviews with both student-athletes, coaches, and academic advisors. Further, a study that employs a mixed-methods approach may be conducted to provide more additional information pertaining to factors of success and perceptions of belonging within this important and unique population.
Keywords: Community college; African American males; Perception; Academic success; Student athlete